Experimental Investigation on the Performance Characteristics of Flow Fields in Redox Flow Batteries Under Various Electrode Parameters - Duan, Z. N.; Zhang, G. B.; Zhang, J. F.; Qu, Z. G. (Frontiers in Thermal Engineering, 2022)
All-vanadium redox flow battery (VRFB) is a promising energy storage technique. Flow fields play a crucial role in distributing the electrolyte into the electrode uniformly, but their performance characteristics under different electrode parameters are still unclear. In this work, taking the total pressure drop and total overpotential as performance characterizations, the influence of electrode parameters and operating conditions on the performance of serpentine flow field (SFF) and interdigitated flow field (IFF) are experimentally investigated. It is found that the battery with IFF exhibits lower pressure drop than that with SFF because of the shunt effect of IFF on electrolyte. In terms of promoting the uniform distribution of the electrolyte into the electrode, the SFF outperforms IFF when the electrode porosity is higher than 0.810, but the performance of SFF and IFF could be reversed as the electrode porosity decreases to 0.714, indicating that there may be a performance reversal between SFF and IFF when the electrode porosity decreases from 0.810 to 0.714. Moreover, the increase of current density, the decrease of electrolyte input and the decrease of electrode thickness strengthen the performance reversal at low electrode porosity. The results well explain the debate on the superiority of IFF and SFF as well as the discussion on the preference between flow fields and electrode thickness in literatures, and provide guidance for the selection of optimal flow field in VRFBs.